2018
DOI: 10.1136/bmjoq-2018-000425
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of hospital-acquired pressure injuries in intensive care and non-intensive care units: a multifaceted quality improvement initiative

Abstract: Hospital-acquired pressure injuries (HAPI) are a significant cause of morbidity and mortality, and represent a major health concern worldwide. Patients suffering from HAPI report a poor quality of life on several dimensions of health. Moreover, HAPI is reported to lengthen in-hospital stay in the acute setting, posing significant healthcare resource utilisations and costs. Given the clinical and economic burden of HAPI, recent best practice guidelines provide recommendations to reduce the prevalence of pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
2
22
0
1
Order By: Relevance
“…Pressure injury (PI), also known as a pressure ulcer, was defined as “a localised injury to the skin and/or underlying tissue usually over a bony prominence, as a result of pressure, or pressure in combination with shear,” (p12) . PI imposes a significant economic and social burden to Australia and globally . The National Pressure Ulcer Advisory Panel, the European Pressure Advisory Panel, and the Pan Pacific Pressure Injury Alliance categorise PIs into six clinical stages (ranging from superficial to deep tissue injuries, including suspected deep tissue injury and unstageable PI); and acknowledge the increase of the negative health impacts with the depth of the PI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure injury (PI), also known as a pressure ulcer, was defined as “a localised injury to the skin and/or underlying tissue usually over a bony prominence, as a result of pressure, or pressure in combination with shear,” (p12) . PI imposes a significant economic and social burden to Australia and globally . The National Pressure Ulcer Advisory Panel, the European Pressure Advisory Panel, and the Pan Pacific Pressure Injury Alliance categorise PIs into six clinical stages (ranging from superficial to deep tissue injuries, including suspected deep tissue injury and unstageable PI); and acknowledge the increase of the negative health impacts with the depth of the PI.…”
Section: Introductionmentioning
confidence: 99%
“…PI imposes a significant economic and social burden to Australia 2 and globally. [3][4][5][6] The National Pressure Ulcer Advisory Panel, the European Pressure Advisory Panel, and the Pan Pacific Pressure Injury Alliance 1 categorise PIs into six clinical stages (ranging from superficial to deep tissue injuries, including suspected deep tissue injury and unstageable PI); and acknowledge the increase of the negative health impacts with the depth of the PI. One of the most common forms of PI are hospital acquired pressure injuries (HAPIs), defined as an area of damage to the skin/ underlying tissue that develops during an inpatient hospital stay.…”
mentioning
confidence: 99%
“…Hospital‐acquired pressure injury (HAPI) is a localized injury to the skin and/or underlying tissue during an inpatient hospital stay. HAPI is a major cause of inpatient morbidity and mortality, making it an important health problem worldwide 1‐3 . Studies on HAPI have found the median incidence to be as high as 10.8% 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Apesar do avanço tecnológico e científico, e do aperfeiçoamento dos serviços e cuidados de prevenção, a incidência de LPP se mantém alta, variando de 10,0% a 62,5%, principalmente em pacientes de unidade de terapia intensiva (UTI), sendo um dos eventos adversos do cuidado mais importantes enfrentados por gestores de saúde (Costa, et al, 2016;Campanili et al, 2015;Sousa et al, 2016;Borghardt, et al, 2015;Agência Nacional de Vigilância Sanitária [ANVISA], 2017;Alderden, et al, 2017;Goodman, et al 2015).…”
Section: Introductionunclassified